When we were friends : a novel - Bourne, Holly (Mira, 2022)
From the day they first meet as teenagers, Fern and Jessica are best friends. Despite their differences, they are there for each other throughout everything, navigating the difficulties of growing up and fitting in. That is, until Jessica crosses a line that Fern can't forgive.